RETRACTED: The influence of the combination of physical and financial capital on the profitability of agricultural formations - Efremenko Innessa; Butkova Oksana (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001